The relationship of pelvic pain symptoms with CA-125 levels in endometriosis cases (Annals of Medical Research, 2021)
Aim: This study aims to investigate the relationship between CA-125 levels and pelvic pain symptoms in patients with endometriosis.Material and Methods: This study consisted of retrospective data of 31 patients who were admitted to the outpatient clinic of Faculty of Medicine, Amasya University between 01 January 2013 and 01 January 2018 for complaints of pelvic pain, dysmenorrhea or infertility, who had a preliminary diagnosis of endometriosis by clinical and ultrasonography examination and diagnosed with endometriosis by laparoscopy or laparotomy as well as 35 patients who received diagnostic laparoscopy for any reason or laparotomy or laparoscopy for benign or tubal ligation. The study included patients aged 18 to 45 years old. Patient data were recorded via an information form which included age, presence of infertility, duration of infertility, preoperative CA-125 values, presence of dysmenorrhea and dyspareunia symptoms, previous operation for endometriosis, presence of additional gynecological pathology, disease stage, operation notes, primary complaints, preoperative TVS information, gravida, parity, abortion and living children, used medication, if any, chronical diseases, if any. Results: The blood CA-125 levels were statistically significant in the patients considering the presence of chronic pelvic pain, dysmenorrhea and infertility (p 0.05). Mean CA-125 levels were 51.43 U/ml in patients with chronic pelvic pain symptoms. Mean CA-125 levels were 45.45 (U/ml) in patients with dysmenorrhea. Mean CA-125 was 45.67 (U/ml) in infertile patients and 45.58 (U/ml) in patients with endometriosis. Mean CA-125 levels in patients with additional gynecological diseases were 38.29 (U/ml), which was not statistically significant.Conclusion: This study demonstrated that CA-125 levels were significantly associated with pelvic pain symptoms, infertility and endometriosis. In light of the results, preoperative serum CA-125 levels are a predictor and should be considered for patients with chronic pelvic pain.Keywords: Endometriosis; CA-125; pelvic pain.
Keywords: Endometriosis; CA-125; pelvic pain.